Developing a Problem-Solving E-Module to Enhance Senior High School Students' Critical Thinking Skills - Karmila Karmila; Nasrun Nasrun; Andi Mulawakkan Firdaus (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to develop and evaluate a problem-solving-based e-module on Sequences and Series to address the low critical thinking skills of senior high school students caused by the lack of interactive learning materials. Methods: Employing a Research and Development (R&D) design with the ADDIE model, the study involved 25 students from SMAN 13 Takalar. Data collected through validation sheets, practicality questionnaires, and pre-test and post-test instruments were analyzed using Aiken’s V formula and Normalized Gain (N-Gain).Findings: The results demonstrated that the developed e-module is highly valid (average 1.00) and categorized as very practical by both practitioners and classroom observations. Furthermore, the e-module proved effective, as evidenced by an average N-Gain of 0.76, placing students' critical thinking improvement in the "high" category. Limitations: However, this study is limited by a small sample size at a single institution, a reliance on purely written cognitive assessments that overlook digital literacy and intrinsic motivation, and the use of a one-group pretest-posttest design without a control group. Research Implications: These findings suggest that integrating structured problem-solving steps into digital modules provides a significant pedagogical tool for teachers to foster higher-order thinking skills. Originality: This research contributes by specifically integrating Polya’s framework with Facione’s cognitive indicators within a culturally contextualized digital e-module.